Razvitak sredstava za plaćanje unaprijed korištenja javnih telefonskih aparata s automatskom naplatom - Mikula, Miroslav (Promet - Traffic&Transportation, 2012)
In order to make possible making phone calls from public places (squares, streets, etc.) as well as shops or restaurants, public phones have been provided that automatically collect the charges. The ways of payment for use of phone have evolved over the years. The paper discusses the ways of collection of charges and provides a review of their features, advantages and disadvantages, and outlooks for the future.